Heterogeneous Labor, Minimum Hiring Standards, and Job Vacancies in Public Employment - Ehrenberg, Ronald G. (Journal of Political Economy, 1973)
[Excerpt] Although a government employer may be the only employer of a particular class of employees in an area (say firemen), it does not necessarily follow that the government agency possesses monopsony power, as current or potential employees can find employment in alternative occupations in the private sector. Moreover, a model is presented in this paper that indicates that the existence of persistent vacancy rates for a class of employees is compatible with there being a greater number of applicants than there are positions, at a wage rate that is predetermined either through a legislative process or collective bargaining. In particular, if applicants vary in quality, then under certain conditions a rational government employer will choose to employ fewer employees than his assumed predetermined authorized employment level. That is, the employer will choose an optimal equilibrium positive vacancy rate.